Summer hot snaps and winter conditions: modelling white syndrome outbreaks on Great Barrier Reef corals. - Scott F Heron; Bette L Willis; William J Skirving; C Mark Eakin; Cathie A Page; Ian R Miller (PLoS ONE, 2010)
Coral reefs are under increasing pressure in a changing climate, one such threat being more frequent and destructive outbreaks of coral diseases. Thermal stress from rising temperatures has been implicated as a causal factor in disease outbreaks observed on the Great Barrier Reef, Australia, and elsewhere in the world. Here, we examine seasonal effects of satellite-derived temperature on the abundance of coral diseases known as white syndromes on the Great Barrier Reef, considering both warm stress during summer and deviations from mean temperatures during the preceding winter. We found a high correlation (r(2) = 0.953) between summer warm thermal anomalies (Hot Snap) and disease abundance during outbreak events. Inclusion of thermal conditions during the preceding winter revealed that a significant reduction in disease outbreaks occurred following especially cold winters (Cold Snap), potentially related to a reduction in pathogen loading. Furthermore, mild winters (i.e., neither excessively cool nor warm) frequently preceded disease outbreaks. In contrast, disease outbreaks did not typically occur following warm winters, potentially because of increased disease resistance of the coral host. Understanding the balance between the effects of warm and cold winters on disease outbreak will be important in a warming climate. Combining the influence of winter and summer thermal effects resulted in an algorithm that yields both a Seasonal Outlook of disease risk at the conclusion of winter and near real-time monitoring of Outbreak Risk during summer. This satellite-derived system can provide coral reef managers with an assessment of risk three-to-six months in advance of the summer season that can then be refined using near-real-time summer observations. This system can enhance the capacity of managers to prepare for and respond to possible disease outbreaks and focus research efforts to increase understanding of environmental impacts on coral disease in this era of rapidly changing climate.